ANALISIS KIMIA 18 JENIS KAYU KURANG DIKENAL DARI JAWA BARAT - Gustan Pari Pari (Jurnal Penelitian Hasil Hutan, 1990)
This paper  deals with  chemieal  analyses  of eighteen  lesser known  wood  species from West Java. The analyses  comprise of  the determination of holocellulose, cellulose,   lignin, pentosan, moisture content, ash. content, silica content and  the solubility in cold  water, hot  water, one percent of sodium hydroxide and alcohol  benzerui extractiue. These   analyses  were conducted  to  determine their  basic characteristics  and  ultimate uses of  the  wood.              The result  shows  that  holocellulose content   ranges from  52,45 - 73,69 percent,   cellulose  from  42,87-58,54 percent, lignin from 20,0 - 31,42  percent,  pentosan from   12,09  - 18,46  percent, moisture content   from 6,84 - 18,62 percent, ash  content from 0,23  - 1,92   persent, silica content   from   0,11 - 0,74 percent. The  solubility in cold  water ranges  from  0,80 - 8,57 percent, hot  water  from  0,84 - 9,64 percent, in one percent sodium hydroxide   solution from 9,07 - 30,34  percent and  in alcohol  benzena (1:2)  from  0,99 - 11,49  percent. Based on chemical analyses, especially the  cellulose  content,  the  18  lesserknown    wood  species  from West  Java  are suitable  as raw material  for pulp  and paper  industry.